Rapid Web-Based Recruitment of Patients With Psoriasis: Multinational Cohort Study - Zacharias Duus Holm; John Robert Zibert; Simon Francis Thomsen; Ari Pall Isberg; Anders Daniel Andersen; Zarqa Ali (JMIR Publications, 2023)
BackgroundWide-ranging patient recruitment not restricted to the location of the investigator will provide a better representation of the patient population in clinical studies. ObjectiveOur goal was to assess the feasibility of a broad web-based recruitment strategy in an 8-week observational study of 500 study participants with psoriasis and healthy controls from locations remote from the investigator and to assess the cost associated with each participant. MethodsA decentralized team in Denmark recruited patients with psoriasis and healthy controls using Google and Facebook advertisements and posts to Facebook groups. All individuals were screened via the internet, and patients diagnosed with psoriasis were included. Questionnaires regarding itch and sleep were completed by both groups at inclusion, week 4, and week 8. ResultsDuring a 2-week recruitment period, 12,887 unique advertisement views were registered, and 839 participants were enrolled, of which 507 completed the study (220 with psoriasis and 287 healthy controls) with a retention rate of 60.4%. Participants were recruited from 11 different countries on 4 separate continents, mainly from the United States, Canada, and the United Kingdom. The recruitment rate was 59.9 participants per day, and the conversion rate was 57.2%. Recruitment costs were US $13 per enrolled participant and US $22 per participant completing the study. ConclusionsIt is feasible and rapid to recruit a large number of participants from locations different from the investigator and to retain patients in an observational study with no visits to a clinical site at low costs.